Willingness and Ability of Older Adults in the Emergency Department to Provide Clinical Information Using a Tablet Computer. Issue 11 (2nd November 2016) - Brahmandam, Sruti; Holland, Wesley C.; Mangipudi, Sowmya A.; Braz, Valerie A.; Medlin, Richard P.; Hunold, Katherine M.; Jones, Christopher W.; Platts‐Mills, Timothy F.
Abstract : Objectives: To estimate the proportion of older adults in the emergency department (ED) who are willing and able to use a tablet computer to answer questions. Design: Prospective, ED‐based cross‐sectional study. Setting: Two U.S. academic EDs. Participants: Individuals aged 65 and older. Measurements: As part of screening for another study, potential study participants were asked whether they would be willing to use a tablet computer to answer eight questions instead of answering questions orally. A custom user interface optimized for older adults was used. Trained research assistants observed study participants as they used the tablets. Ability to use the tablet was assessed based on need for assistance and number of questions answered correctly. Results: Of 365 individuals approached, 248 (68%) were willing to answer screening questions, 121 of these (49%) were willing to use a tablet computer; of these, 91 (75%) were able to answer at least six questions correctly, and 35 (29%) did not require assistance. Only 14 (12%) were able to answer all eight questions correctly without assistance. Individuals aged 65 to 74 and those reporting use of a touchscreen device at least weekly were more likely to be willing and able to use the tablet computer. Of individuals with no or mild cognitive impairment, the percentage willing to use the tablet was 45%, and the percentage answering all questions correctly was 32%. Conclusion: Approximately half of this sample of older adults in the ED was willing to provide information using a tablet computer, but only a small minority of these were able to enter all information correctly without assistance. Tablet computers may provide an efficient means of collecting clinical information from some older adults in the ED, but at present, it will be ineffective for a significant portion of this population.